2013
DOI: 10.7785/tcrt.2012.500319
|View full text |Cite
|
Sign up to set email alerts
|

Acute Radiation Esophagitis Caused by High-Dose Involved Field Radiotherapy with Concurrent Cisplatin and Vinorelbine for Stage III Non-small Cell Lung Cancer

Abstract: Purpose of this study is to obtain dose-volume histogram (DVH) predictors and threshold values for radiation esophagitis caused by high-dose involved field radiotherapy (IFRT) with concurrent chemotherapy in patients with stage III non-small cell lung cancer (NSCLC).Thirty-two patients treated by 66 Gy/33 Fr, 72 Gy/36 Fr, and 78 Gy/39 Fr thoracic radiotherapy without elective nodal irradiation plus concurrent cisplatin and vinorelvine were reviewed.Acute radiation esophagitis was evaluated according to common … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
(50 reference statements)
0
9
0
Order By: Relevance
“…In the study by Kuroda et al keeping esophagus V35 ≤20% was associated with a considerably lower risk of esophagitis, which is more conservative than the QUANTEC V35 constraint. [46] In two separate reports, keeping the esophagus V50 <11%[49] or <50%[48] was identified as the optimal cutoff points for grade ≥2 or ≥3 esophagitis, respectively, which agrees reasonably well with the QUANTEC constraint. In a cohort of lung cancer patients treated with SBRT, keeping the esophagus D 5cc ≤26.3 GyBED 10 or max dose ≤52.9 GyBED 10 was associated with <20% risk of grade ≥2 esophagitis.…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…In the study by Kuroda et al keeping esophagus V35 ≤20% was associated with a considerably lower risk of esophagitis, which is more conservative than the QUANTEC V35 constraint. [46] In two separate reports, keeping the esophagus V50 <11%[49] or <50%[48] was identified as the optimal cutoff points for grade ≥2 or ≥3 esophagitis, respectively, which agrees reasonably well with the QUANTEC constraint. In a cohort of lung cancer patients treated with SBRT, keeping the esophagus D 5cc ≤26.3 GyBED 10 or max dose ≤52.9 GyBED 10 was associated with <20% risk of grade ≥2 esophagitis.…”
Section: Resultsmentioning
confidence: 64%
“…Thus, differences in patient characteristics, treatment setup and systemic therapy should be considered when using these dose-volume constraints to inform HNC OAR sparing. Acute esophagitis is typically assessed by physician-scoring using CTCAE[4648, 51, 52] and EORTC/RTOG[49, 5355] scales, although one study reported on patient-reported esophagitis based on EORTC QLQ-C30. [56]…”
Section: Resultsmentioning
confidence: 99%
“…V 50 was also the significant predictor for RE ≥grade 3 in the study by Kwint et al 4 Zhang et al 19 demonstrated that, in CCRT, V 40 was the significant factor associated with grade ≥2 RE (33.3% as V 40 <23% vs 89.1% as V 40 ≥23%) and V 50 was significantly correlated with grade 3 RE (6.7% as V 50 <26.5% vs 38.7% as V 50 ≥26.5%). Kuroda et al 5 revealed that V 35 was the only dosimetric predictor for grade ≥2 RE on multivariate analysis. Caglar et al 20 found that D mean and V 45 –V 60 were significantly associated with the risk of grade ≥3 RE.…”
Section: Resultsmentioning
confidence: 99%
“…Nineteen studies graded RE using RTOG criteria, while one study used the common toxicity criteria 4 and another used the common terminology criteria. 5 We summarized the results from five aspects as below.…”
Section: Resultsmentioning
confidence: 99%
“…Several dosimetric factors were identi ed as predictors of RE including mean oesophageal dose (Dmean) [3] and volume of the oesophagus (Vx) receiving greater than 35 Gy (V35) [4], 40 Gy (V40) [5], 50 Gy (V50) [5,6], and 60 Gy (V60). Dosimetric factors [7,8] contain only partial dose distribution information.…”
Section: Introductionmentioning
confidence: 99%